Genotypic variability for tolerance to salinity and phosphorus deficiency among N-2-dependent recombinant inbred lines of Common Bean ([i]Phaseolus vulgaris[/i]) - L'Taief, Boulbaba; Sifi, Bouaziz; Zaman-Allah, Mainassara; Horres, Ralf; Molina, Carlos; Beebe, Steve; Winter, Peter; Kahl, Guenter; Drevon, Jean-Jacques; Lachaâl, Mokhtar (African journal of microbiology research, 2012)
Common bean (Phaseolus vulgaris L.) is often subject to various environmental constraints including soil salinity and phosphorus deficiency as major limitations for the yield of most grain legumes, especially when the plant growth depends upon N-2 fixation. In order to assess the genetic variation for tolerance to moderate salinity and phosphorus deficiency and identify the related morphological, physiological and genetic traits, 37 common bean recombinant inbred lines (RILs) were inoculated with Rhizobium tropici CIAT899, and grown in a glasshouse with 25 mM NaCl or 75 mu mol P plant(-1) week(-1), compared to optimal nutrient solution in hydroaeroponic culture system. Large genotypic variation in tolerance to P deficiency and salt was found with some RILs being tolerant to both constraints. By contrast some of the RILs showed tolerance to only one constraint while the most sensitive to salinity were also sensitive to P-deficiency. By using 18 microsatellite primer-pairs with six most contrasting RILs, 4 alleles were found to discriminate among the RILs. It is concluded that these genotypes and the microsatellites primers can be used to identify genes involved in salinity and P deficiency tolerance of N-2-dependent legume.